Remmus Othiambo talks about how his community can work together for a better tomorrow - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In May, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) gender team held several sessions pre-testing an upcoming "Socially Inclusive Participatory Research and Development for Climate Change and Food Security" guide. This took part in Kenya, where we also talked to the participants on what they learned and got out of the participatory sessions.